CYBER SEXUAL HARASSMENT IN HIGHER EDUCATION: CHALLENGES AND LEGAL PERSPECTIVES IN THE POST-PANDEMIC ERA - Chakraborty, Swati; Lata, Parvesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The shift to online education during the COVID-19 pandemic has brought about significant challenges, including a rise in cybersexual harassment (CSH) in academic settings. The anonymity of the internet makes it difficult to identify harassers, posing unique challenges compared to in-person harassment. While CSH was a concern prior to the pandemic, the transition to predominantly virtual learning environments has exacerbated the issue, with online spaces offering new opportunities for harassment. This study explores the impact of CSH on higher education, particularly in the post-pandemic context, and examines the limitations of existing legal frameworks in addressing harassment in virtual environments. Although online education has improved accessibility, it has also introduced risks, such as cyber abuse. Existing sexual harassment laws offer some recourse for victims, but explicit regulatory measures for online spaces remain limited. Despite considerable research on CSH, its prevalence and impact within higher education have received insufficient attention, raising concerns as online education continues to grow. Addressing CSH is essential for fostering a safe and supportive online learning environment in the post-pandemic world